2015
DOI: 10.1152/ajplung.00261.2014
|View full text |Cite
|
Sign up to set email alerts
|

Plasma vascular endothelial growth factor A and placental growth factor: novel biomarkers of pulmonary hypertension in congenital diaphragmatic hernia

Abstract: Patel N, Moenkemeyer F, Germano S, Cheung MM. Plasma vascular endothelial growth factor A and placental growth factor: novel biomarkers of pulmonary hypertension in congenital diaphragmatic hernia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…It is often used in the studies of other diseases such as pregnancy complicated by hypertensive disorders, pulmonary hypertension and preeclampsia [3537]. Previous study demonstrated that it contributed to angiogenesis and plasma extravasation in ischemia and other pathological conditions [21].…”
Section: Discussionmentioning
confidence: 99%
“…It is often used in the studies of other diseases such as pregnancy complicated by hypertensive disorders, pulmonary hypertension and preeclampsia [3537]. Previous study demonstrated that it contributed to angiogenesis and plasma extravasation in ischemia and other pathological conditions [21].…”
Section: Discussionmentioning
confidence: 99%
“…Various growth factor signaling pathways seem to be involved in the pathogenesis of human CDH (6,7,44,60) as well as in the lung response after experimental TO (6,64). Transforming growth factor (TGF)-␤ is a key player in lungbranching morphogenesis and alveolization (5).…”
mentioning
confidence: 99%
“…19,20 Plasma VEGF levels were found elevated and correlated with clinical severity of pulmonary vascular disease in infants with CDH. 21 Furthermore, the authors report a most obvious pattern of increased VEGF in the first week of life in CDH patient, who did not survive and postulate a critical early postnatal period in VEGF-mediated pulmonary vascular development. Our results are rather in accordance with reports of reduced VEGF in infants with acute persistent pulmonary hypertension.…”
Section: Discussionmentioning
confidence: 97%